A Preliminary European-Scale Assessment of Microplastics in Urban Wastewater - Obermaier, Nathan; Pistocchi, Alberto (Frontiers in Environmental Science, 2022)
Microplastics are not well defined from an analytical point of view, and their measurement in the environment is still challenging. At the same time, their increasingly widespread presence is raising concerns for human health and ecosystems. In this contribution, we present a preliminary European-scale assessment of the environmental input of microplastics through urban wastewater. We quantify the emissions associated to urban wastewater based on the range of observed concentrations in wastewater treatment plants (WWTPs) effluents, and the emissions from tire wear particles (TWP) by assuming that a percentage of the particles generated on roads eventually reaches surface waters. In spite of the large uncertainties entailed in the calculation, it is apparent that TWP dominate the input of total plastic loads into European surface waters. The management of urban and road runoff as well as combined sewer overflows (CSO) is therefore essential in order to control overall plastics emissions. On the other hand, WWTPs are able to retain the majority of plastics in the sewage sludge. The spreading of sewage sludge onto soil therefore represents an additional pathway of plastics from urban wastewater into the environment.